Can Open Science be a Tool to Dismantle Claims of Hardwired Brain Sex Differences? Opportunities and Challenges for Feminist Researchers. (December 2021) - Persson, Sofia; Pownall, Madeleine
Feminist scholars have long been concerned with claims of hardwired brain sex differences emanating from neuroscience and evolutionary psychology. Past criticisms of these claims have rightfully questioned the impact of this research on gender equality, pointing out how findings can be used to vindicate gender stereotypes. In this article, we appraise the brain sex differences literature through the lens of open science, a movement aimed at improving the robustness and reliability of science. In this discussion, we offer a feminist evaluation of the strategies (e.g., pre-registration, data sharing, and accountability) provided by open science, and we question whether these may be the novel and disruptive tools needed to dismantle claims about hardwired brain sex differences. We suggest that open science strategies can be useful in challenging some of these claims, and we note that promising initiatives are already being developed in neuroscience and allied fields. We end by acknowledging the distinct challenges that feminist researchers wishing to engage in open science face, particularly in the context of limited diversity. We conclude that open science presents considerable opportunity for feminist researchers, and that it will be crucial for feminists to be involved in shaping the future of this movement.